Global Stability of a Parabolic System Involving a Nonlinear Diffusion Operator with an Example in Epidemiology (Journal of Nonlinear Modeling and Analysis, 2025)
The purpose of this work is to study the global stability of specificnonlinear parabolic equations incorporating the $p$-Laplacian operator, witha primary emphasis on their application in biology, particularly in the context of epidemiology. This investigation entails the construction of Lyapunovfunctions derived from the associated ODEs. To elucidate our approach, weprovide an illustrative example from the field of epidemiology.